Topical Issues of Modern Directing Education - Pogrebnіak, Galyna (Vìsnik Kiïvsʹkogo nacìonalʹnogo unìversitetu kulʹturi ì mistectv. Serìâ: Audìovìzualʹne mistectvo ì virobnictvovyrobnytstvo, 2022)
The purpose of the research is to identify the problems of training directors in the field of audiovisual art and production; to outline the prospects for modernization of the educational process in higher educational institutions of artistic direction in Ukraine. The research methodology is based on the methods of scientific analysis, comparison, and generalization. Analytical and systematic methods were used to study the art historical aspect of the problem. The empirical method was used to observe and study the educational process and production practice in the Kyiv National I K. Karpenko-Kary Theatre, Cinema and Television University, Kyiv National University of Culture and Arts, and Kyiv University of Culture. The scientific novelty of the study is that the problem of directing education in Ukraine in the context of the state support programs functioning time became the subject of a special study for the first; the concept’s content of “directing education” as specific integrity and unity of interrelated elements is argued; the worldview principles of training directors in the field of audiovisual art and production are singled out and characterized; the expediency of using communicative methods in the educational process of training directors is proved. Conclusions. Familiarization with the materials presented in the article expands the arsenal of knowledge about the specifics of providing quality educational services in higher education institutions of artistic direction in Ukraine and enables their use in pedagogical practices.